Barriers to accessing the culturally sensitive healthcare that could decrease the disabling effects of arthritis in a rural Mayan community: a qualitative inquiry. Issue 5 (May 2016) - Loyola-Sanchez, Adalberto; Richardson, Julie; Wilkins, Seanne; Lavis, John; Wilson, Michael; Alvarez-Nemegyei, Jose; Pelaez-Ballestas, Ingris
Abstract The impact of living with arthritis in a rural Mexican Mayan community along with the barriers encountered by people living with this chronic condition were investigated in this study. The community needs around this health issue were investigated by conducting an ethnographic study using data obtained during two time periods (August 2012–April 2013 and December 2013–December 2014). During the first period, fieldwork observations and interviews with 65 individuals, which included people with arthritis, health professionals, traditional health providers, and community leaders were undertaken. During the second period, 46 community meetings were conducted to identify the needs associated with arthritis in the municipality. Data were analyzed following a modified version of theFramework approach. The results show that arthritis reduces the health-related quality of life of the people in Chankom through a process of disablement, conditioning a need to access culturally sensitive healthcare. Availability, attainability, and acceptability barriers prevent access to this type of healthcare and result from power imbalance between indigenous and non-indigenous people. There is a need to develop culturally sensitive rehabilitation services for people living with arthritis in Chankom. Mayan people should be involved in the design and implementation of these services. Moreover, it is important to improve our understanding of the processes behind the healthcare access inequities identified in this study by attending to the historical generation of current social, economical, cultural, and political structures.